Cadherin expression, vectorial active transport, and metallothionein isoform 3 mediated EMT/MET responses in cultured primary and immortalized human proximal tubule cells. - Andrea Slusser; Chandra S Bathula; Donald A Sens; Seema Somji; Mary Ann Sens; Xu Dong Zhou; Scott H Garrett (PLoS ONE, 2015)
Cultures of human proximal tubule cells have been widely utilized to study the role of EMT in renal disease. The goal of this study was to define the role of growth media composition on classic EMT responses, define the expression of E- and N-cadherin, and define the functional epitope of MT-3 that mediates MET in HK-2 cells.Immunohistochemistry, microdissection, real-time PCR, western blotting, and ELISA were used to define the expression of E- and N-cadherin mRNA and protein in HK-2 and HPT cell cultures. Site-directed mutagenesis, stable transfection, measurement of transepithelial resistance and dome formation were used to define the unique amino acid sequence of MT-3 associated with MET in HK-2 cells.It was shown that both E- and N-cadherin mRNA and protein are expressed in the human renal proximal tubule. It was shown, based on the pattern of cadherin expression, connexin expression, vectorial active transport, and transepithelial resistance, that the HK-2 cell line has already undergone many of the early features associated with EMT. It was shown that the unique, six amino acid, C-terminal sequence of MT-3 is required for MT-3 to induce MET in HK-2 cells.The results show that the HK-2 cell line can be an effective model to study later stages in the conversion of the renal epithelial cell to a mesenchymal cell. The HK-2 cell line, transfected with MT-3, may be an effective model to study the process of MET. The study implicates the unique C-terminal sequence of MT-3 in the conversion of HK-2 cells to display an enhanced epithelial phenotype.